Production Management Of Ngantri Program On Radio Suara Gontor FM - Diah Rukmini; Fiki Putra Muayad; Nurhana Marantika (SAHAFA: Journal of Islamic Communication, 2026)
Suara Gontor FM is one of the media or a forum for disseminating information and da›wah of PondokModern Darussalam Gontor which has many programmes for the delivery of its da›wah, one of which is theNgantri programme. With the existence of the Ngantri programme, parents can listen directly to what theirstudents feel in the pesantren. The Ngantri programme can also be a reference for prospective parents whowant to send their children to the pesantren. This research uses descriptive qualitative methods, by goingdirectly to the field for more in-depth analysis. The data collection techniques in this research are interviews,observation, and documentation. To maintain the existence of this program so that it remains popular withmany listeners, it needs good management, which is in accordance with the four basic functions of management,namely planning, organising, implementing, and supervising. The supervision function is to set the vision andmission, direction and goals, and objectives of the Ngantri programme. The organising function is to assign human resources to the structure as well as the division of labour so that implementation occurs effectively and efficiently. The implementation function includes the process of directing and influencing the Suargo FM crew to be enthusiastic in carrying out their responsibilities. The supervision function is to ensure that the work goes according to plan and is able to achieve the goals that have been designed together, this supervision includes the process of assessment and evaluation.Keywords: Management; Ngantri program; Radio